2002
DOI: 10.1046/j.1365-2923.2002.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalisability: a key to unlock professional assessment

Abstract: A G-study uses variance component analysis to measure the contributions that all relevant factors make to the result (observer, situation, case, assessee and their interactions). This information can be combined to reflect the reliability of a single observation as a reflection of all possible measurements - a true reflection of reliability. It can also be used to estimate the reliability of a combined sample of several different observations, or to predict how many observations are required with different tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 5 publications
1
131
1
Order By: Relevance
“…The most traditionally used psychometric analysis for OSCEs is generalisability theory (Crossley, Davies, Humphris, & Jolly, 2002). Generalisability analysis works best when examiners are fully "crossed" with students and stations (i.e., all examiners observe all students at all stations); however, the model can produce useful data when some partial crossing is available (Shavelson, Webb, & Rowley, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The most traditionally used psychometric analysis for OSCEs is generalisability theory (Crossley, Davies, Humphris, & Jolly, 2002). Generalisability analysis works best when examiners are fully "crossed" with students and stations (i.e., all examiners observe all students at all stations); however, the model can produce useful data when some partial crossing is available (Shavelson, Webb, & Rowley, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Content specificity underpins this variability and accounts for more variation than the rest of the identified sources combined. This is a common finding in generalizability study analyses 27 and illustrates the concept that the perceptions (and subsequent ratings) of any one interviewer along with his/her specific questions greatly affect an assessment's reliability; therefore, multiple interviewers should be sought. Using 8 interviewers within 8 separate interview stations was more reliable than having all 8 interviewers as 1 panel/station or even having 2 interviewers to 4 interview stations.…”
Section: Discussionmentioning
confidence: 78%
“…[25][26][27][28][29] The specific software program used herein was G_Strings IV, version 6.1.1 (Hamilton, ON, CA). The results output from a generalizability study will provide the relative contributions of different variance sources to variance in the entire data set, with a generalizability coefficient reported for reliability of the entire process (0.0-1.0 scale; similar to Cronbach's alpha).…”
Section: Phase Twomentioning
confidence: 99%
“…28 Using G-theory, important findings from OSCE-based evaluations have revealed that a global rating scale for each station (instead of a detailed checklist) was at least as reliable as a checklist over the multiple OSCE stations. 29 Regarding validity evidence, they also demonstrated that, among medical students, residents and physicians, global rating scales were able to detect changes in growing clinical expertise that checklists could not capture.…”
Section: Generalizability Theorymentioning
confidence: 99%